PTU-070 Patient-Reported Quality of Life During Golimumab Induction for Moderate to Severe Ulcerative Colitis in the United Kingdom: Results from The Go-Colitis Study. (17th August 2016) - Irving, P; Probert, C; Gaya, D; Hamlin, PJ; Sebastian, S; Gillespie, G; Tate, H; Wheeler, C
Abstract : Introduction: Consistent relief of symptoms is among the most important attributes considered by patients with ulcerative colitis (UC) when selecting a therapy. 1 GO-COLITIS (NCT02092285 ; 2013–004583-56) is a UK phase 4, multicentre, open-label, single-arm trial of golimumab (GLM) for the treatment of moderate to severe UC. Here, we report the results of an analysis of patient-reported quality of life (QoL) at the end of the GLM induction phase. Methods: Anti-TNF naive patients (≥18 y) with UC ≥ 3 months and with moderate to severe disease (partial Mayo score 4–9 or full Mayo score 6–12) at baseline, Mayo rectal bleeding subscore ≥1, and endoscopy subscore ≥2 (if full Mayo was used) were included. Patients received subcutaneous GLM on day 0 (200 mg) and day 14 (100 mg) during the 6 week induction phase, followed by GLM 50 or 100 mg every 4 weeks during the 48 week maintenance phase with 12 week follow-up, in line with the Summary of Product Characteristics. Patients completed the Inflammatory Bowel Disease Questionnaire (IBDQ) and EuroQoL Group 5 Dimensions Health Questionnaire (EQ-5D) at baseline and at week 6 during GLM induction. Data were summarised descriptively. Results: 205 patients were enrolled (mean [range] age, 39.3 [18–79] years; male, n = 123 [60%]). All patients received one or two doses of induction GLM. Statistically significant improvements from baseline to induction week 6 (mean [SD]) were observed for IBDQ total score (Baseline: 115.9 (32.4); week 6: 161.9 (38.2); change from baseline of 45.2 [37.4] (p < 0.0001), as well as the individual IBDQ domains of bowel symptoms, emotional function, systemic symptoms, and social function (all p < 0.0001). In addition, significant improvements in the EQ-5D index score (0.1 [0.2]; p < 0.0001) and health state visual analogue scale (VAS) (15.6 [26.6]; p < 0.0001) were observed Conclusion: During the GLM induction phase of the GO-COLITIS study, patients with moderate to severe UC experienced significant improvements from baseline in disease-specific QoL, including bowel symptoms, emotional function, systemic symptoms, and social function, as well as generic QoL. Reference: 1 GreyGray JR, et al. Aliment Pharmacol Ther 2009;29 :1114–1120. Disclosure of Interest: P. Irving Grant/research support from: MSD, Takeda, Consultant for: Abbvie, Warner Chilcott, Takeda, MSD, Vifor Pharma, Pharmacosmos, Topivert, Genentech, Hospira, Speaker bureau with: Abbvie, Falk Pharma, Ferring, MSD, Shire, Takeda, Warner Chilcott, Johnson and Johnson, C. Probert Consultant for: Abbvie, MSD, Napp, Takeda, Speaker bureau with: Abbvie, Ferring, Falk Pharma, MSD, Shire, Takeda, Conflict with: Abbvie, Falk Pharma, MSD, Shire, Takeda, D. Gaya Speaker bureau with: Abbvie, Falk Pharma, Ferring, MSD, Shire, Takeda, Vifor, Conflict with: Abbvie, Falk Pharma, MSD, Shire, Takeda, Vifor, P. Hamlin Speaker bureau with: Abbvie, Ferring, MSD, Takeda, Warner Chilcott, Tillots, Conflict with: Abbvie, Falk Pharma, MSD, Tillotts, S. Sebastian Grant/research support from: Abbvie, Ferring, Warner Chilcott, Johnson and Johnson, Consultant for: Falk Pharma, Ferring, MSD, Takeda, Vifor, Warner Chilcott, Speaker bureau with: Abbvie, Takeda, Warner Chilcott, G. Gillespie Shareholder of: MSD UK, Conflict with: Employment: MSD UK, H. Tate Consultant for: MSD UK, C. Wheeler Shareholder of: MSD UK, Conflict with: Employment: MSD UK